Effect of Intranasal Oxytocin Administration on Human-Directed Social Behaviors in Shelter and Pet Dogs - Barrera, Gabriela; Dzik, Victoria; Cavalli, Camila; Bentosela, Mariana (Frontiers in Psychology, 2018)
A wide variety of evidence has demonstrated that oxytocin is involved in socio-cognitive 21 skills in domestic dogs (Canis familiaris). The purpose was to evaluate the effect of 22 oxytocin administration on socio-cognitive abilities in two populations of dogs with 23 different levels of daily human contact: shelter and pet dogs. Additionally, the effect of 24 different doses of oxytocin (i.e. 16 and 24 IU) was assessed. To this end, dogs were tested 25 on two tasks: a sociability test to assess their social responses and a communicative task 26 focused on the learning of gazing responses. Results showed that pet dogs performed better 27 than shelter dogs on the sociability and the gazing test, showing the relevance of dogs’ 28 previous experience and learning when interacting with people. The administration of 16 29 IU as well as 24 IU of oxytocin improved the performance on the communicative learning 30 task, producing an increment in gaze duration during extinction. This difference was 31 observed in both pet and shelter dogs. Therefore, oxytocin seems to participate in the 32 persistence of this communicative response. However, the treatment did not modify the 33 behaviors during the sociability test. Furthermore, oxytocin appears to be beneficial to 34 increase the communicative abilities of shelter dogs.